Práticas obstétricas e influência do tipo de parto em resultados neonatais e maternos em Sergipe - Prado, Daniela Siqueira (2018)
Background: Brazil has high frequency of inappropriate obstetric practices and cesarean sections. This procedure may be associated with increased maternal and perinatal morbidity. Objective: to describe practices and interventions used during labor and childbirth and factors associated with such practices and to evaluate the impact of mode of delivery in breastfeeding incentive practices and in neonatal and maternal complications. Methods: A Cohort study was conducted, between june 2015 and april 2017, at the 11 maternity hospitals in Sergipe with 768 puerperal women, interviewed in the first 24 hours after delivery, 45-60 days and 6-8 months after delivery. The associations between good practices and interventions used during labor and delivery with exposure variables were described by simple frequencies, percentages, crude and adjusted odds ratios (ORA) with the confidence interval and the association between breastfeeding incentive practices, neonatal and maternal, both short term and late complications and the exposure variables were evaluated by the relative risk (95% IC) and the Fisher exact test. Results: were fed 10.6% of women and 27.8% moved during labor; non-pharmacological measures for pain relief were performed in 26.1%; the partograph was filled in 39.4% of the charts and the companion was present in 40.6% of deliveries. Oxytocin, amniotomy and analgesia occurred in 59.1%, 49.3% and 4.2% of women, respectively. The delivery occurred in the lithotomy position in 95.2% of the cases, there was episiotomy in 43.9% and Kristeller's maneuver in 31.7%. The factors most associated with cesarean section were the private health sector (ORA = 4.27,95% CI: 2.44-7.47), had higher education (ORA = 4.54,95%CI 2.56 -8.3) and high obstetric risk (ORA = 1.9,95%CI: 1.31-2.74). Private-sector users had a greater presence of the companion (ORA = 2.12,95% CI:1.18-3.79) and analgesia (ORA = 4.96,95% CI:1.7-14.5). The C-section delivery resulted in less skin-to-skin contact immediately after delivery (intrapartum c-section: RR=0.18;95%CI:0.1-0.31 and elective c-section: RR=0.36;95%CI:0.27-0.47) and less breastfeeding within one hour of birth (intrapartum C-section: RR=0.43;95%CI:0.29-0.63 and elective C-section: RR=0.44;95%CI:0.33-0.59). Newborns from elective c-section were less frequently breastfed in the delivery room (RR=0.42;95%CI:0.2-0.88) and stayed less in rooming- in (RR=0.85;95%CI:0.77-0.95). Women who were submitted to intrapartum c-section had greater risk of early complications (RR=1.3;95%CI:1.04-1.64; p=0.037) and sexual dysfunction (RR=1.68;95%CI:1.14-2.48; p=0.027). There was no difference in the frequency of neonatal complications, urinary incontinence and depression according to the mode of delivery. Conclusions: good obstetric practices are poorly performed and unnecessary interventions are frequent, and the factors most associated with cesarean delivery have been the private health sector, higher schooling and high obstetric risk. C-section was negatively associated to breastfeeding incentive practices. C-section after labor increased the risk of early maternal complications and sexual dysfunction, six to eight months after delivery.